Overlap Syndrome and Myasthenia Gravis: An Uncommon Association With Unusual Features. Issue 4 (April 2019) - Ray, Gautam
Abstract : ABSTRACT: The author presents a rare case of overlap syndrome associated with myasthenia gravis in the absence of acetylcholine receptor antibody and thymoma. Various liver autoantibodies developed at different times later in the disease course and myasthenia occurred 5 years after the diagnosis of liver disease. The importance of repeating antibody panel later in the disease course for proper diagnosis and timely treatment is highlighted. The exact mechanism of the development of myasthenia gravis in autoimmune liver disease also needs investigation for the possibility of new drug development that might be beneficial to both.